EVALUASI KEBIJAKAN PENGGUNAAN DANA KUTE TAHUN 2023 DI KABUPATEN ACEH TENGGARA - Habib Habibi; Riyan Jaelani; Vinda Verina Kartika Dewi Primasari (Fakultas Politik Pemerintahan IPDN, 2025)
This study evaluates the policy of using the 2023 Kute Fund in Southeast Aceh Regency, focusing on its implementation, supporting factors, and inhibitions. The importance of this evaluation lies in the need for Kute funds to be on target, adequate, and contribute to improving people's welfare. This research employs a descriptive qualitative approach, utilizing data collection techniques that include interviews, observations, and documentation. Furthermore, the data is analyzed by reducing it, presenting the results, and drawing conclusions. The results of the study show that the Kute Fund policy in Southeast Aceh Regency in 2023 is generally running well, but faces obstacles in terms of effectiveness and accuracy, especially related to the allocation of funds that are not always in accordance with priorities and the lack of capacity of the Kute apparatus in budget management. Factors that support success include regulatory support, community involvement, and a commitment from local government. Inhibiting factors include the low competence of Human Resources, the lack of socialization of regulations, and public pressure on the use of funds that do not comply with the provisions. This study recommends increasing the capacity of the Kute apparatus, strengthening the internal supervision system, and providing continuing education to the public on the use of Kute funds in accordance with development priorities. Keywords: Public policy, Policy evaluation, Kute fund.